2015
DOI: 10.1128/jvi.03614-14
|View full text |Cite
|
Sign up to set email alerts
|

Genome Diversity of Epstein-Barr Virus from Multiple Tumor Types and Normal Infection

Abstract: Epstein-Barr virus (EBV) infects most of the world's population and is causally associated with several human cancers, but little is known about how EBV genetic variation might influence infection or EBV-associated disease. There are currently no published wild-type EBV genome sequences from a healthy individual and very few genomes from EBV-associated diseases. We have sequenced 71 geographically distinct EBV strains from cell lines, multiple types of primary tumor, and blood samples and the first EBV genome … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

36
343
1
8

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 219 publications
(388 citation statements)
references
References 50 publications
36
343
1
8
Order By: Relevance
“…The EBV genome encodes fewer proteins than the vaccinia virus genome but many more than the genome of HIV or influenza virus, providing ample structural proteins to serve as CD4 T-cell epitopes. In agreement with our findings, previous analyses of available full-length EBV genomes, although mostly from cell lines and tumors, have shown the gp350 gene to be one of the least variable genes, suggesting that our measurements of gp350 gene variation may significantly underrepresent the total viral genome variation (18).…”
Section: Figsupporting
confidence: 81%
See 1 more Smart Citation
“…The EBV genome encodes fewer proteins than the vaccinia virus genome but many more than the genome of HIV or influenza virus, providing ample structural proteins to serve as CD4 T-cell epitopes. In agreement with our findings, previous analyses of available full-length EBV genomes, although mostly from cell lines and tumors, have shown the gp350 gene to be one of the least variable genes, suggesting that our measurements of gp350 gene variation may significantly underrepresent the total viral genome variation (18).…”
Section: Figsupporting
confidence: 81%
“…Recent studies, including our own, have demonstrated that dsDNA viruses can exhibit levels of variation similar to those observed in some RNA viruses, such as West Nile virus and HIV-1 (16,17). Most published EBV gp350 sequences have originated from either transformed B-cell lines or cancerous tissue; at present, only a very limited number of primary EBV gp350 sequences are available (18). A better understanding of the diversity of circulating EBV gp350 sequences, as well as the potential role of EBV-specific antibodies in the evolution of EBV gp350 diversity over time in infected individuals, would be helpful to inform vaccine development.…”
mentioning
confidence: 99%
“…EBNA1 is the only viral protein consistently expressed during all forms of latency and in all EBV-associated malignancies (9,10). It is potentially a universal target for immune recognition of EBV-infected normal or malignant cells (10).…”
Section: Discussionmentioning
confidence: 99%
“…EBNA1 is the only viral protein consistently expressed during all forms of latency and in all EBV-associated malignancies (9,10). It is potentially a universal target for immune recognition of EBV-infected normal or malignant cells (10). The series of essential components for a humoral immune response, including NA1-expressed cells, APCs (HLA-DR+, CD80+ and CD86+), T helper cells (CD3+ and CD4+) and B cells (CD19+ and IgA+), were all detected by IHC staining in the local tumor environment.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation